Complete mitochondrial genome sequences of the Arctic Ocean codfishes Arctogadus glacialis and Boreogadus saida reveal oriL and tRNA gene duplications - Breines, Ragna; Ursvik, Anita; Nymark, Marianne; Johansen, Steinar Daae; Coucheron, Dag-Hugo (Polar Biology, 2015)
Paid Open Access